Capital structure and impact of debt maturity structure on firms leverage level in Malaysia - Cheng, Fan Fah; Ng, Huey Chyi (SAS Publishers (Scholars Academic and Scientific Publishers), 2018)
The main objective of a firm’s manager is maximizing shareholders’ wealth while trying to achieve optimum capital structure. Having too much of debts could increase the firm’s risk level while it might help to take up good investment opportunities and bring in positive cash flow in future. On the other hand, holding low leverage level to maintain lower liquidity risk might cause the firm to sacrifice any great investment opportunity. This causing under investment and agency problem between the firm’s managers and shareholders. Thus, various issues and factors need to be considered while deciding on a firm’s capital structure and financing decisions. Firms debt maturity structure can affect the liquidity risk in a firm as well as the firm’s borrowing power. Having too much short term debts will reduce the firm’s borrowing power and causing a higher liquidity risk, whereby firm’s managers need to ensure they have enough cash flow for debt repayments while the debt is due for payment in short term. Long term debts could reduce the liquidity risk but causing a higher cost to the firm. Thus, this study is to investigate the firms’ capital structure while focusing on the impact of debt maturity on firm’s leverage level together with other factors. Results indicated that firms in Malaysia are following pecking order theory whereby firms prefer to use internal funds compare to debts. The firms’ debt maturity structure, tax shields, investment activities and firms size was found with significant positive impact on firms’ leverage level. Conversely, firms’ profitability, dividend payout ratio and economics conditions were found with significant negative impact on the firms’ debt level. This paper provides a better understanding on the Malaysian firms’ capital structure and guiding the firms’ manager in managing firms’ debt level and avoiding bankruptcy.